Changes in Caries Experience, Untreated Caries, Sealant Prevalence, and Preventive Behavior among Third-Graders in New York State, 2002–2004 and 2009–2012. (July 2015) - Kumar, Jayanth V.; Tavares, Vinicius; Kandhari, Priyanka; Moss, Mark; Jolaoso, I. Adeyemi
Objective: This study assessed changes in caries experience, untreated caries, sealant prevalence, and preventive behavior among third-grade children in New York State to monitor progress toward state health objectives. Methods: We analyzed children's data from the 2002–2004 ( n =10, 865) and 2009–2012 ( n =6, 758) New York State Oral Health Survey. We calculated differences in weighted percentages and 95% confidence intervals for caries experience, untreated caries, sealant prevalence, and preventive behavior. We used logistic regression procedures to assess the independent effects and interaction terms on dental caries experience. Results: The percentage of children with dental caries and untreated caries decreased from 54.1% and 33.0% in 2002–2004 to 45.2% and 23.6% in 2009–2012, respectively. While this decrease was not uniform across income subgroups, the prevalence of sealants, a key measure of the use of preventive services, increased significantly from 16.7% to 36.0% among lower-income children. Conclusions: Measurable improvement in reducing dental caries prevalence among third-grade children has been made in New York State, but this improvement was not uniform across subgroups. Specifically, disease prevalence among lower-income children remained high, underscoring the need to strengthen existing programs and identify additional policy and programmatic interventions.